Novel technologies and theoretical models in radiation therapy of cancer patients using 6.3 MeV fast neutrons produced by U-120 cyclotron; AIP Conference Proceedings; Vol. 1760 : Physics of Cancer: Interdisciplinary Problems and Clinical Applications 2016 - Musabaeva L. I.; Startseva Zh. A.; Gribova O. V.; Velikaya V. V.; Lisin V. A. (2016, 2016)
Title screen